2020
DOI: 10.1139/cjss-2019-0110
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregate stability increased with a self-regenerating legume cover crop in low-nitrogen, no-till agroecosystems of Saskatchewan, Canada

Abstract: Black medic (Medicago lupulina L.) is a self-regenerating cover crop which was tested for its ability to improve soil physical properties. Soil aggregate stability was assessed in plots that included a black medic cover crop in a no-till grain rotation, which was fertilized with two levels of nitrogen (N), for 15 yr. In the wheat phase of the rotation, the medic cover crop increased mean weight diameter by 21% in the reduced N fertilizer treatment but not in the recommended N treatment. Generally, the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Legumes such as soybeans and mucuna pruriens have well-developed root systems which can fix plants to absorb nutrients and water through soybeans. In the study of April Stainsby et al [38], legumes improved the stability of aggregates, which is consistent with the results of this study. In OW //M treatment, compared with legumes, watermelon has a weaker role of plant roots and a greater damage to soil stability.…”
Section: Effects Of Different Intercropping Methodssupporting
confidence: 93%
“…Legumes such as soybeans and mucuna pruriens have well-developed root systems which can fix plants to absorb nutrients and water through soybeans. In the study of April Stainsby et al [38], legumes improved the stability of aggregates, which is consistent with the results of this study. In OW //M treatment, compared with legumes, watermelon has a weaker role of plant roots and a greater damage to soil stability.…”
Section: Effects Of Different Intercropping Methodssupporting
confidence: 93%
“…This indicates a benefit of the self‐regenerating cover crop in terms of the water economy of the cropping system. Possible reasons for the increase in WUE with medic at the low N rate include greater grain yield (i.e., an increase in the numerator of the WUE equation; Table 11), less water loss to evaporation because of an increased thickness in soil surface residue with a cover crop (Thapa et al., 2021), and improvements in soil physical properties (Stainsby et al., 2020),…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is improvements in soil physical properties from the medic. For example, Stainsby et al (2020) observed an increase in macroaggregates in these medic plots and greater macroag- .…”
Section: 9mentioning
confidence: 92%
See 2 more Smart Citations